PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPS KONSEP KEMISKINAN - Lisnawati Iskandar Alam (PEDAGOGIK, 2021)
This research was conducted with the aim of improving the learning outcomes of fourth grade students at SD Negeri 49 Ternate on the concept of poverty through the use of a contextual learning model using the inquiry method. The research design is classroom action research (Classroom Action Research) with the instruments used are test questions, teacher and student observation sheets, and interviews. The data analysis technique used is descriptive qualitative.Based on the data analysis, it is concluded that the use of the contextual model of the inquiry method can improve learning outcomes on the concept of poverty. This can be shown by the acquisition of the average score of student learning outcomes of 60.52% (cycle I) increased to 78.94% (cycle II). In addition, student learning activities increased as indicated by the acquisition of the average activity score (cycle I) increased to 89.96% (cycle II). The use of the inquiry method contextual learning model can also improve students' learning mastery, namely the number of students who complete learning in the first cycle is 8 students (42%) increasing to 15 students (79%) in the second cycle of the number of students 22 students. In addition, the activities of the teaching and learning process of teachers increased as indicated by the acquisition of an average score of 62.5% (cycle I) increased to 87.5% (cycle II).